Compassion fatigue and satisfaction among frontline staff in long term care facilities: psychometric properties of the Serbian version of the professional quality of life scale - Vracevic, Milutin; Pavlovic, Vedrana; Todorovic, Natasa; Milic, Natasa M.; Matejic, Bojana; Brkic, Predrag; Milic, Nikola V.; Savic, Marko; Masic, Srdjan; Pavlovic, Andrija; Stanisic, Vladislav; Tasic, Ana; et al. (Frontiers in Psychiatry, 2025)
IntroductionThis study explored the complex relationship between anxiety, depression, compassion fatigue, and satisfaction among long-term care (LTC) workers following the COVID-19 pandemic. In addition, the study assessed psychometric properties of the Professional Quality of Life (ProQOL) scale, to ensure a reliable and valid instrument for identifying compassion fatigue and satisfaction in the Serbian healthcare system.MethodsA cross-sectional study was conducted across LTC facilities in the Republic of Serbia. A ProQOL was administered to physicians, nurses, and aids, to measure compassion fatigue (including burnout and secondary traumatic stress) and compassion satisfaction. The following standardized instruments were also distributed: Secondary Traumatic Stress Scale (STSS), Depression Anxiety and Stress Scale 21 (DASS-21) and 12-Item Short-Form Health 36 Survey (SF-12).ResultsA total of 300 LTC workers participated, mostly women (86.3%), with an average age of 45.4 ± 10.5 years and a median work experience of 15 years (range: 1 to 42 years). The study reported a significant presence of anxiety and depression symptoms (53.3% and 43.3%, respectively), with LTC workers experiencing moderate levels of compassion fatigue, as indicated by burnout (58.3%) and stress (57.3%) subscales, and moderate or high levels of compassion satisfaction (49.0% and 50.0%, respectively). The study demonstrated that anxiety impacts depression both directly and indirectly (p<0.05). Specifically, burnout and compassion satisfaction mediated the positive effect of anxiety on depression, indicating that increased anxiety led to higher burnout and lower compassion satisfaction, which resulted in greater depression (p<0.05). The three-factor structure of the ProQOL was validated (IFI, TLI, and CFI were above the cut-off of ≥0.95, and the RMSEA was below the suggested value of ≤ 0.06). The Cronbach α of the three subscales was above 0.8, indicating good scale reliability.ConclusionThis study contributes to the broader literature on LTC workers wellbeing by examining the complex interplay between professional quality of life, anxiety, and depression. The findings should guide decision-makers in developing targeted interventions and policies that promote the psychological resilience and well-being of LTC workers, thereby enhancing both individual and organizational outcomes in the healthcare sector.